PENGEMBANGAN MODUL PEMBELAJARAN IPA UNTUK PEROLEHAN BELAJAR SISWA PADA MATERI PERUBAHAN ZAT KELAS VII SMPN 6 KETAPANG - Hamidi Hamidi; Aunurrahman Aunurrahman; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to design science learning modules, the appearance and acquisition of learning outcomes on material chemistry changes class VII SMP Negeri 6 Ketapang. This study involved media experts, teacher colleagues, individula tests, small groups and large groups. The subjects of this study were students class VII SMP Negeri 6 Ketapang. Data obtained from observations, interviews, documentation and test questions. This research uses research and development. The results of this study produce a learning product, the learning module. Development research carried out combines the steps of Borg & Gall's development with the Dick and Carey model. The results showed that the modules used were suitable for use. This is based on the results of the trial of individual groups with the "good" category, a small group test "good" and a large group test "good". The results of the validation of media experts showed results in the "good" category. For learning outcomes, this science learning module shows that there is an increase in student learning outcomes before using the learning module and after using the learning module. The increase in learning outcomes was seen in the mean score of pretest 44,1 and the mean posttest score of 97,2. Statistical test using t test shows that the value of t arithmetic is - 46.99 and t table is 1.697 (α 5%). Thus it was concluded that the learning process using the learning module was better than without learning modules.  Keywords: Learning Module, Learning Acquisition, Substance Change